Mali : Technical Assistance Report. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Assistance Report for Mali examines the performance of its public expenditure management system. The IMF report suggests that payments arrears can possibly be monitored overtime through the financial management system (PRED), based on the validation of invoices. The principle of requiring funds to be deposited in the Treasury must be clearly reinstated and observed. It recommends that agencies benefiting largely from subsidies or direct public financing should transfer funds in order of priority. Stock and assets accounting is being gradually implemented and rolled out as planned, with new software being currently deployed for line departments' managers.